á¼”Ï„Î¹ á¼”Î½Î¹Î±Î¹ Ï„á¿¶Î½ Ï€Î±ÏÎ¿Î¹Î¼Î¹á¿¶Î½ ÎºÎ±á½¶ Î³Î½á¿¶Î¼Î±Î¯ Îµá¼°ÏƒÎ¹Î½ (Arist. Ret. 1395a12). LA RELACIÓN ENTRE SENTENCIA Y PROVERBIO EN LA RETÓRICA DE ARISTÓTELES (Stylos, 2019)
This article addresses the existent relationship between gnÁ´mai and the paroimíai in Aristotele’s Rhetoric, having into consideration that this author was the first one to methodize the use of gnÁ´mai in rhetoric speech, defining them theoretically. To stablish the relationship between one and the other type of statements, we will start with the confirmation done in 1395a12 about the fact that, in some circumstances, a proverb is a sentence: á¼”Ï„Î¹ á¼”Î½Î¹Î±Î¹ Ï„á¿¶Î½ Ï€Î±ÏÎ¿Î¹Î¼Î¹á¿¶Î½ ÎºÎ±á½¶ Î³Î½á¿¶Î¼Î±Î¯ Îµá¼°ÏƒÎ¹Î½ (“even some proverbs are sentences too”). First, I take the gnÁ´mai in the form they are presented in Rhetoric II. Secondly, I make a survey of the paroimíai from book I. Ultimately, I remark similarities and differences between both types of statements.
Keywords: sentence – proverb – rhetoric – Aristotle